2011
DOI: 10.4315/0362-028x.jfp-11-118
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements and Metals in Farmed Sea Bass and Gilthead Bream from Tenerife Island, Spain

Abstract: The aim of this study was to determine the levels of metals (Ca, K, Na, Mg) and trace metals (Ni, Fe, Cu, Mn, Zn, Pb, Cd) in two fish species (gilthead bream [Sparus aurata] and sea bass [Dicentrarchus labrax]) collected from fish farms located along the coast of Tenerife Island. Ca, K, Na, Mg, Fe, Cu, Zn, and Mn were measured by flame atomic absorption spectrometry, whereas Pb, Cd, and Ni were determined using graphite furnace atomic absorption spectrometry. Mean Fe, Cu, Mn, and Zn contents were 3.09, 0.59, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Abubakar et al [ 61 ] noted a much higher iron content in the muscles of Scomber scombrus from Nigeria (11.453 mg/kg and 21.873 mg/kg) and found that these values were above the recommended safety limits provided by the FAO/WHO. Rubio et al [ 62 ] found that a daily average consumption of 45.8 g of Gilthead seabream from Tenerife fish farms (Spain) provided 0.29 mg of Fe (1.6–3.6% of the RDA), 0.062 mg of Cu (6.89–8.86% of the RDA) and 0.83 mg of Zn (7.58–10.43% of the RDA). According to the RDA (Recommended Dietary Allowances) standard, the daily requirement for Cu is 0.9 mg/day in all analyzed age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Abubakar et al [ 61 ] noted a much higher iron content in the muscles of Scomber scombrus from Nigeria (11.453 mg/kg and 21.873 mg/kg) and found that these values were above the recommended safety limits provided by the FAO/WHO. Rubio et al [ 62 ] found that a daily average consumption of 45.8 g of Gilthead seabream from Tenerife fish farms (Spain) provided 0.29 mg of Fe (1.6–3.6% of the RDA), 0.062 mg of Cu (6.89–8.86% of the RDA) and 0.83 mg of Zn (7.58–10.43% of the RDA). According to the RDA (Recommended Dietary Allowances) standard, the daily requirement for Cu is 0.9 mg/day in all analyzed age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metals are released into the environment from natural and human sources such as sewage sludge, municipal solid wastes, metal-based pesticides and fertiliz ers, and industrial emissions (2,15,16,30,32,34). Tubers accumulate metals from the environment through their roots and foliar surfaces.…”
mentioning
confidence: 99%
“…In humans, prolonged oral exposure to excessive Cd causes renal tubular dysfunction, bone fragility, and reproductive disorders. In contrast, Pb mainly affects the central nervous system of fetuses and infants, and elevated exposure levels have been linked to hemotoxic effects, gastrointestinal tract alterations (" saturnine colic" ), nephropathies, and Alzhei mer's disease in adults (2,29,30,35).…”
mentioning
confidence: 99%